Exercise in youth: High bone mass, large bone size, and low fracture risk in old age - Tveit, M.; Rosengren, B. E.; Nilsson, J. A.; Karlsson, M. K. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Physical activity is favorable for peak bone mass but if the skeletal benefits remain and influence fracture risk in old age is debated. In a cross-sectional controlled mixed model design, we compared dual X-ray absorptiometry-derived bone mineral density (BMD) and bone size in 193 active and retired male elite soccer players and 280 controls, with duplicate measurements of the same individual done a mean 5 years apart. To evaluate lifetime fractures, we used a retrospective controlled study design in 397 retired male elite soccer players and 1368 controls. Differences in bone traits were evaluated by Student's t-test and fracture risk assessments by Poisson regression and Cox regression. More than 30 years after retirement from sports, the soccer players had a Z-score for total body BMD of 0.4 (0.1 to 0.6), leg BMD of 0.5 (0.2 to 0.8), and femoral neck area of 0.3 (0.0 to 0.5). The rate ratio for fracture after career end was 0.6 (0.4 to 0.9) and for any fragility fracture 0.4 (0.2 to 0.9). Exercise-associated bone trait benefits are found long term after retirement from sports together with a lower fracture risk. This indicates that physical activity in youth could reduce the burden of fragility fractures.